2011
DOI: 10.1130/ges00570.1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Sierra Nevada from receiver functions and implications for lithospheric foundering

Abstract: Receiver functions sampling the Sierra Nevada batholith and adjacent regions exhibit signifi cant variations in the structure of the crust and upper mantle. Crustal Vp/Vs values are lower in the core of the batholith and higher in the northern Sierra Nevada, portions of the Basin and Range, and near young volcanic fi elds in the eastern Sierra Nevada and Owens Valley. P-to S-wave conversions from the Moho vary from high amplitude and shallow (>25% of the direct P-arrival amplitude, 25-35 km depth) along the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(155 citation statements)
references
References 112 publications
(202 reference statements)
12
142
0
Order By: Relevance
“…Resulting SV hypocentral depths are consistent with Moho depths determined from receiver functions at this latitude [Frassetto et al, 2011]. Cross sections D′ and P′ of Frassetto et al [2011] show Moho depths in the vicinity of the deep swarms within a range of 30-35 km.…”
Section: Geophysical Research Letterssupporting
confidence: 67%
“…Resulting SV hypocentral depths are consistent with Moho depths determined from receiver functions at this latitude [Frassetto et al, 2011]. Cross sections D′ and P′ of Frassetto et al [2011] show Moho depths in the vicinity of the deep swarms within a range of 30-35 km.…”
Section: Geophysical Research Letterssupporting
confidence: 67%
“…The absence of a Ps signal could be caused by a steeply dipping Moho pulled down by a dripping lower lithosphere (18). However, later work showed that this weak Ps conversion is not confined to the vicinity of the Isabella anomaly; it extends along the entire western Sierra Nevada and is now thought to be due to the presence of a dense mafic-ultramafic residue in the lower crust that reduces the contrast between crust and mantle (20), an interpretation that is consistent with our tomography model that has unusually high S-wave velocities in the lower crust beneath the western Sierra Nevada (Fig. 3C).…”
Section: Discussionmentioning
confidence: 99%
“…The crust of the Colorado Plateau between parts of the Rockies and Basin and Range exhibits a broad transition over a wide depth interval between the crust and mantle, with crustal thicknesses between 40 and 45 km (Wilson et al, 2005). Along the western margin of the Basin and Range, the crust thickens into the Sierra Nevada to as much as 40 km or more (e.g., Ruppert et al, 1998;Fliedner et al, 2000;Frassetto et al, 2011). Crustal thicknesses close to 40 km continue farther to the north of the Sierra Nevada into the active Cascade volcanic arc, to the east of which the crust thins in the backarc to close to 30 km within the High Lava Plains (Cox and Keller, 2010;Eagar et al, 2011).…”
Section: Previous Investigationsmentioning
confidence: 99%